Assessing the Effectiveness of International Climate Agreements in Mitigating Global Warming - Mravcová, Anna (Studia Ecologiae et Bioethicae, 2025)
This paper provides an in-depth evaluation of the effectiveness of international climate agreements in addressing the issue of global warming. As concern about climate change increase, global collaboration has become crucial in designing and implementing strategies to reduce emissions of greenhouse gases. The study reviews major international agreements, including the Kyoto Protocol, the Paris Agreement, and the subsequent Kyoto Climate Agreement, exploring their internal mechanisms, goals, and results. Drawing on empirical data, it assesses how well these agreements have performed in real life as regards limiting the global warming. The paper also discusses the challenges and obstacles in the process of implementing the agreements, such as compliance difficulties, political hurdles, and the involvement of various stakeholders. By synthesizing current research and policy insights, the paper aims to enhance public understanding of the effectiveness of these agreements and provides recommendations for improving their impact in tackling the urgent threat of climate change.